What triggered the catastrophic 15 January 2022 Hunga eruption? - Jie Wu; Shane J. Cronin; Marco Brenna; Joali Paredes-Mariño; Sung-Hyun Park; Mila Huebsch; Alessio Pontesilli; Chris Firth; David Adams; Teresa Ubide; Kyle Hamilton; Alice MacDonald; et al. (Earth and Planetary Science Letters, 2026)

A cautionary tale of disequilibria in microlite-melt evolution driven by fast crystallization kinetics: Implications for modeling volcanic processes - Jie Wu; Alessio Pontesilli; Marco Brenna; Shane J. Cronin; Sung-Hyun Park; Joali Paredes-Mariño; Kyle Hamilton; Marta Ribó; David Adams; Mila Huebsch (Earth and Planetary Science Letters, 2026)

Sensory applications of natural language processing and text analysis in practice: a review of recent literature - Kyle Hamilton; Rebekah J Miller; Jacob Lahne (Current Opinion in Food Science, 2026)

Perturbation solution for second-harmonic generation in focused shear wave beams in soft solids - Philip G. Kaufinger; John M. Cormack; Kyle S. Spratt; Mark F. Hamilton (Wave Motion, 2025)

Understanding perceptions of unfamiliar drinks using natural language in simulated drinking contexts - Kyle Hamilton; Julien Delarue (Food Quality and Preference, 2025)

Flavor language in expert reviews versus consumer preferences: An application to expensive American whiskeys - Kyle Hamilton; Clinton L. Neill; Jacob Lahne (Food Quality and Preference, 2023)

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

The impact of microsatellite electromorph size homoplasy on multilocus population structure estimates in a tropical tree ( Corythophora alta ) and an anadromous fish ( Morone saxatilis ) - RACHEL I. ADAMS; KYLE M. BROWN; MATTHEW B. HAMILTON (Molecular Ecology, 2004)
Microsatellite allelic states are determined by electrophoretic sizing of polymerase chain reaction fragments to define electromorphs. Numerous studies have documented that identical microsatellite electromorphs are potentially heterogeneous at the DNA sequence level, a phenomenon called electromorph size homoplasy. Few studies have examined the impact of electromorph size homoplasy on estimates of population genetic parameters. We investigated the frequency of microsatellite electromorph size homoplasy for 12 loci in the tropical tree Corythophora alta and 11 loci in the anadromous fish Morone saxatilis by sequencing 14–23 homozygotes per locus sampled from multiple populations for a total of 453 sequences. Sequencing revealed no homoplasy for M. saxatilis loci. Seven C. alta loci exhibited homoplasy, including single and compound repeat motifs both with and without interruptions. Between 12.5 and 42.9% of electromorphs sampled per locus showed size homoplasy. Two methods of correction for homoplasy in C. alta generally produced little or no change in single‐locus estimates of R ST , except for two loci in which some additional differentiation among populations was revealed. Twelve‐locus estimates of R ST (including the seven loci corrected for homoplasy) were slightly greater than estimates from uncorrected data, although the 95% confidence intervals overlapped. The frequency of methodological errors such as clerical mistakes or sample mislabelling per genotype scored was estimated at 5.4 and 7.3% for C. alta and M. saxatilis , respectively. Simulations showed that the increase in R ST produced by homoplasy correction was only slightly larger than variation in R ST estimates expected to be caused by methodological errors.